Marchiafava-Bignami Disease in a Nonalcoholic Diabetic Patient. (24th April 2013) - Yadala, Sisira; Luo, Jin Jun
Abstract : Marchiafava-Bignami disease (MBD) is a rare neurological disorder mostly seen in alcoholic and malnourished patients with a pathognomonic hallmark of corpus callosum demyelination. MBD in nonalcoholics without malnutrition has rarely been reported. We report a case of MBD in a diabetic patient, without alcoholism or malnutrition, caused by a wide range of glycemic level fluctuations. A 38-year-old man presented with sudden onset of alteration in speech and multiple falls in three days. Neurologic examination showed dysarthria, dysmetria, and ataxia but, otherwise, normal cranial nerves, motor and sensory functions, and tendon reflexes. Brain MRI showed symmetric abnormalities in the splenium of the corpus callosum. In addition, demyelination was also observed in bilateral posterior limbs of the internal capsule and brachium ponti. His symptoms significantly improved after stabilization and normalization of his plasma glucose level and administration of multivitamins and corticosteroids. The underlying pathophysiology of the development of MBD in our case is likely to be osmotic stress from a wide range of glycemic fluctuations causing structural and functional disturbance of oligodendrocytes, which may be reversible in its early stage.